Development of Community Participation-Based Tourism Village in Genggelang Village, Lombok Utara District - Taufiq Kurniawan; Lala Nining Indrawati; Intan Maharani Asmara (Journal on Education, 2023)
The problems studied in this research are related to the development of the Genggelang Tourism Village, North Lombok Regency, regarding the forms of participation carried out by the community. The research method used is descriptive with a qualitative approach. Data collection techniques included observation, interviews, and documentation with informants comprising the Tourism Awareness Group of Penjor Hamlet, Tourism Awareness Group of Kertaraharja Hamlet, and Tourism Awareness Group of Gangga Hamlet. The results of this study indicate that the forms of community participation are divided into four forms of participation, the so-called the participation of money, assets, labor and skills. This form of community participation is based on the supporting and inhibiting factors that exist in Genggelang Tourism Village. The supporting and inhibiting factors are divided into three hamlets, where each hamlet has a tourist destination. Thus, the form of community participation in Genggelang Tourism Village is also divided in each related hamlet. The information contained in this research is expected to be able to help increase community participation in Genggelang Tourism Village, North Lombok Regency.